Teacher Education Reform in Far East Russia: Integrating Field Experiences with Action Research - Grigory A. Kapranov; Alexander W. Chizhik; Estella W. Chizhik (Educational Process: International Journal)
In 2011, the Russian Far Eastern Federal University teacher education faculty redesigned field-experience practica to improve teacher candidates’ professional reflection, practical classroom instruction, and capacity for action research. For each academic year, faculty aspired to achieve these goals by collaborating to develop field experiences that differentiated mentoring of teacher candidates to fit with their professional goals and preparation levels. The purpose for this study is to investigate the effectiveness of this reform by comparing pre-reform senior theses to post-reform senior theses on a series of outcomes. Using a mixed-methods approach, findings indicate that post-reform teacher candidates outperformed pre-reform candidates on thesis quality. Specifically, post-reformed candidates were better able to make theoretical connections to their practice as evidenced by their action research topics and findings.